Protectors or praetorians? : the last Mamlūk sultans and Egypt's waning as a great power - Petry, Carl F., 1943- (SUNY series in medieval Middle East history., 1994)
This analysis of state policy under the last two Mamluk rulers enables modern readers to observe a pivotal era in the history of Egypt and southwest Asia. Beset with external threats and internal dissent, the Mamluk Sultanate confronted profound challenges in its waning years. The author depicts how each monarch differed in his response to the bureaucratic and military dilemmas he faced. Al-Ashraf Qaytbay remained a stalwart conservator of traditional soldierly values. He would be revered by later generations as an exemplary officer and pious believer. Qansuh Al-Ghawri, however, exhibited little regard for hallowed traditions, military or religious. Burdened by irremedial bankruptcy and endemic sedition, he initiated the first steps toward innovation since the architects of the Mamluk system founded the regime during the thirteenth century.